Everyday guides made easy Apple iOS & iPhone basics - Smith, Chris (Flame Tree Publishing, 2015)
Apple created iOS, the incredible operating system that their iPhones use. With so many apps and new features being added all the time, this book will help you to get started. Learn how to use this great modern system in a way that is suited to your needs. This handy guide will take you through the best apps, tips and tricks for everyday use and has a troubleshooting guide if you get into trouble. With step-by-step instructions and clear, practical text, a novice to the iPhone will learn everything they need to know.